The impact of illicit drug networks on the effectiveness of law enforcement in South Africa - Machethe, Petrus; Mofokeng, Jacob Tseko (Technium Social Sciences Journal, 2022)
In the past few years, South Africa has experienced an enormous increase in the amount and types of illicit drug manufacturing, distribution and use. This has resulted in an increase in the burden of crime and health risks in the community. The patterns of drug availability and drug use have been linked to regional and country variations, socio-economic status, racial and geographical differences. Because of the dramatic increase in the availability of various illicit drugs, the United Nations Office on Drugs and Crime World Drug Report (2012) identified South Africa as one of the drug centres of the world. This raises concerns about whether law enforcement agencies perform their functions effectively. This paper focuses on the illicit drug networks that hinder the effectiveness of law enforcement in South Africa. The modus operandi used to produce and smuggle illicit drugs and the challenges experienced by law enforcement to prevent and combat illicit drugs will be discussed. The data was collected through in-depth interviews with experts within the criminal justice system in South Africa. The study conducted in 2017/ 2018 in terms of the scientific measurements, has adopted a qualitative approach. Data was collected from a target population consisting of 11 SAPS drug-related crime experts, including members of the SAPS specialised detectives of the Directorate for Priority Crime Investigation (DPCI), crime intelligence members, border police, the International Criminal Police Organisation (INTERPOL) and commanders at ports of entries. A documentary study was used as a secondary method of data collection. Data obtained from interviews were analysed by identifying common themes from the respondents’ descriptions of their experiences.